Tree Physiology Optimization tuning rule for Proportional-Integral control - Halim, A.H.; Ismail, I. (EDP Sciences, 2017)
This paper presents a tuning correlation for Proportional-Integral (PI) controller parameters using Tree Physiology Optimization algorithm (TPO). TPO is a metaheuristic algorithm that has parallel search strategy inspired from plant growth system. The parallel search is referred to the plant branches and leaves that able to diversify the search space and therefore finding promising results in much faster iterations. The exploration is amplified from roots growth counterparts. In the proposed method, a tuning correlation of PI-controller using TPO is established and the performances of correlated parameters are compared with Ciancone correlation. The idea of correlation tuning is to reduce the optimization time consumption and engineering efforts in controller tuning. The results shown that the tuning correlation of TPO is able to find good PI parameters with lesser error. © The authors, published by EDP Sciences, 2017.